Role of Studio Exercises in Digital Design Education Case Study of the Nine-Square Grid - Yazar, Tugrul; Pakdil, Oya (ECAADE-EDUCATION & RESEARCH COMPUTER AIDED ARCHITECTURAL DESIGN EUROPE, 2009)
This paper is about short term and contextually limited kit-of-parts exercises in architectural education. Studio exercises are one of the key educational tools in architecture, which should be reconsidered with the developing technologies. As design computing becomes the mainstream thinking in architecture, the need for not only renewed studio exercises but for new educational frameworks becomes an essential issue. Thus, in this paper we will be proposing a different perspective on digital studio education, by explaining the fundamentals of studio exercises and their digital transformation potentials. Our experience with one of the most common kit-of-parts exercises, the nine-square grid, as a computational design problem for the first year students will be presented here as a part of this on going study.
Keywords: Digital design education; learning models; studio exercises; the nine-square grid.; Architecture